Legal landscape of trust law in Thailand: the fading twilight of common law trusts and the sunrise of statutory trusts. Issue 8 (5th August 2021) - Reekie, Adam; Reekie, Surutchada; Ruengsrichaiya, Kaipichit
Abstract: The creation of trusts in Thailand was strictly prohibited by the adoption of the Civil and Commercial Code in 1935. However, this civil law jurisdiction is currently home to a number of trusts: those created prior to 1935 in accordance with English law and trusts for use in capital markets, a statutory exception introduced in 2008. With a bill introducing trusts for personal asset management in the legislative pipeline, this article presents a timely overview of this little-known but evolving trust law landscape.